2013
DOI: 10.2217/nnm.12.136
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Inflammatory Death of Monocytes and Macrophages by Overtaking of A Critical Dose of Endocytosed Synthetic Amorphous Silica Nanoparticles/Serum Protein Complexes

Abstract: The physiological specialization of monocytes/macrophages to effectively capture NPs may expose them to the risk of catastrophic inflammatory death upon saturation of their maximal storage capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…The above-documented synergy of SiO 2 NPs and bacterial EMs in inducing the production of IL-1␤ and other cytokines was specific for dendritic cells. In fact, in agreement with previous observations (51), in monocytes SiO 2 NPs alone were sufficient to induce IL-1␤ and TNF-␣ above a concentration threshold (100 g/ml), and EMs weakly modulated or did not modulate such effects (Fig. S4).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The above-documented synergy of SiO 2 NPs and bacterial EMs in inducing the production of IL-1␤ and other cytokines was specific for dendritic cells. In fact, in agreement with previous observations (51), in monocytes SiO 2 NPs alone were sufficient to induce IL-1␤ and TNF-␣ above a concentration threshold (100 g/ml), and EMs weakly modulated or did not modulate such effects (Fig. S4).…”
Section: Resultssupporting
confidence: 93%
“…This does not exclude the possibility that other myeloid antigen-presenting cells (monocytes and macrophages) or non-antigen-presenting cells, such as leukocytes (e.g., polymorphonuclear neutrophil granulocytes [PMNGs]), could also be subjected to synergic effects upon stimulation with NPs and microbes. It has been demonstrated that amorphous silica nanoparticles are endocytosed by macrophages (51) and that incubation with increasing amounts of silica NPs increased the percentages of dead cells and the parallel induction of proinflammatory cytokine IL-1␤ release. In fact, formyl peptide receptor agonists have been shown to synergize cytokine production by monocytes and the chemotactic response in PMNGs in the presence of SiO 2 NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Simple geometric considerations make it however difficult to rationalize, especially for small nanoparticles (<30 nm diameter), the physical coexistence in the same corona of hundreds of different protein types, in particular when one considers that some of them have a size comparable to or even larger than the NP itself. 23,24 With these cells, SiO 2 -NP capture in FCS is very high and comparable to that observed in protein free media. [12][13][14] This observation somehow resolves the paradox of accommodating too many components in the same corona, but introduces an additional level of heterogeneity of the corona-coated NPs, because it implies the presence of several subsets of nanoparticles each characterized by its own corona, with fewer polypeptides but with specific composition differences.…”
Section: Introductionmentioning
confidence: 52%
“…Low nanoparticle doses (<40 µg ml −1 ) were used both to avoid potential confounding factors arising from cytotoxic and proinflammatory effects and to better simulate the high dilution conditions presumably experienced by nanoparticles after injection in the bloodstream. 23,24 The behaviour observed in human plasma (HP) is substantially different. 1).…”
Section: Differential Effect Of Fcs and Hp On Sio 2 -Np Macrophage Bimentioning
confidence: 99%
“…It has been convincingly shown that some nanoparticles can accumulate in immune cells, such as macrophages (Buono et al 2009;Arnida et al 2011;Lunov et al 2011;Fedeli et al 2013;Gasparotto et al 2013). However, the degree of accumulation that occurs in humans after NP exposure is unknown.…”
Section: Role Of Immune Cellsmentioning
confidence: 99%